Teachers negotiating multilingualism in the EFL classroom - Pitkänen-Huhta Anne; Mäntylä Katja (De Gruyter Mouton, 2022)
This article sets out to explore English as foreign language (EFL) teachers’
views of teaching migrant pupils with multilingual backgrounds in a regular
classroom. Previous studies on multilingual pupils have mostly concentrated
on second language learning contexts or on the role of pupils’ L1. In an increasingly
multilingual world and due to growing migration, this study concentrates
on EFL. The data were interviews with English teachers (n=7), who reflected on
their experiences with migrant pupils in the foreign language classroom. The data
were analysed through qualitative content analysis. The participants had not
really pondered on the role of multilingualism in the EFL classroom and some
underlying preconceptions could be detected. Teachers’ perception of the multilingual
pupil was controversial in that they did not want to draw attention to the
linguistic background of the pupil but, on the other hand, they had noticed that
multilingual learners had greater language awareness than their mainstream
peers. Although not fully aware of the potential of multilingualism and the pupils’
linguistic resources in EFL teaching, the teachers had used several ways of supporting
their multilingual learners, reflecting the principles of translanguaging.